Analisis pengendalian persediaan pasir pada perusahaan beton dengan metode Economic Order Quantity dan metode Min-Max - Safitri, Aurelia Ayu; Dewi, Sinta (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Raw materials are very important in the production process. If raw materials are lacking, production can be delayed. On the other hand, if there is too much, the company will incur additional costs to store it. This research aims to find out how much sand (the main raw material in making concrete) should be ordered each time so that there is no shortage of raw materials, but also not to waste money on costs. storage. There are two methods used to calculate the ideal order quantity: first, the EOQ (Economic Order Quantity) method and second, the Min-Max method. The results show that by using the EOQ method, the company can save costs of IDR 19,102,570 compared to the Min-Max method. So, the EOQ method is considered more suitable to be applied in this concrete company because it is more efficient in managing sand supplies.